2002
DOI: 10.1081/iph-120003749
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitrostyrene on Cell Proliferation and Macrophage Immune Responses

Abstract: The use of mood enhancing drugs such as amphetamine and ecstasy are now prevalent in society. These compounds are known to produce serious psychological and physiological problems in users, which can, in some circumstances result in death. While there has been much research into the effects of these drugs on the body, little if any research has investigated the effect of the side products and synthetic reaction by-products which are a consequence of there illegal production. In the study the effects of nitrost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…One of these derivatives showed potent antiproliferative effects on mouse epidermal keratinocyte cell line. Furthermore, treatment of nitrostyrene has a significant suppressive effect on the proliferation of the stomach cancer cell line (Carter et al, 2002). The results in this study revealed the molecular mechanism of action of nitrostyrene derivatives as telomerase inhibitors.…”
Section: Discussionmentioning
confidence: 67%
“…One of these derivatives showed potent antiproliferative effects on mouse epidermal keratinocyte cell line. Furthermore, treatment of nitrostyrene has a significant suppressive effect on the proliferation of the stomach cancer cell line (Carter et al, 2002). The results in this study revealed the molecular mechanism of action of nitrostyrene derivatives as telomerase inhibitors.…”
Section: Discussionmentioning
confidence: 67%
“…In recent years, there have been many studies investigating the biological effects and functions of these compounds, with nitrostyrenes having been shown to have antimicrobial 39,41 and insecticidal 42 properties. Some have even been shown to affect the down regulation of interleukins, suggesting an immunological role 43 .…”
Section: Insert Figmentioning
confidence: 99%
“…1 These compounds have also been described as highly potent and selective human telomerase inhibitors 2 as well as cytotoxic for human cancer cell lines. 3 Moreover, it was shown that they are able to downregulate the production of some interleukins, thus affecting the immune response in humans. 3 The nitrovinyl side chain attached to the aromatic ring was recognized to be an essential chemical feature in this type of compounds and a critical conformational pattern for their biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…3 Moreover, it was shown that they are able to downregulate the production of some interleukins, thus affecting the immune response in humans. 3 The nitrovinyl side chain attached to the aromatic ring was recognized to be an essential chemical feature in this type of compounds and a critical conformational pattern for their biological activity. 1,4 Although the antifungic and antibacterial properties of this type of compounds have been studied since the 1940s, the work in this area during the last decade is rather scarce.…”
Section: Introductionmentioning
confidence: 99%